Understanding the Three Types of the First Semester Learners in English Language Education Study Program - Pratama, Ryan Andhika (Universitas Negeri Semarang, 2019)
Every learner has their own learning styles, and there are three types of learner; such as visual learner, auditory learner, and kinesthetic learner. This paper will talk about the three types of learners based on their learning styles, the classification of English Language Education Study Program students based on the three types of learners, and what should the teachers do to help them to achieve the greater knowledge while learning new things. The research using the VAK Learning Styles Self-Assessment Questionnaire obtained from Swinburne University of Technology. The result shows that from the total of 153 students, there are 47% visual type learners, 36% auditory type learners and 17% kinesthetic type learners.